If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (24x + -23) + (12x + -13) + (12x + -13) + 11y = 360 Reorder the terms: (-23 + 24x) + (12x + -13) + (12x + -13) + 11y = 360 Remove parenthesis around (-23 + 24x) -23 + 24x + (12x + -13) + (12x + -13) + 11y = 360 Reorder the terms: -23 + 24x + (-13 + 12x) + (12x + -13) + 11y = 360 Remove parenthesis around (-13 + 12x) -23 + 24x + -13 + 12x + (12x + -13) + 11y = 360 Reorder the terms: -23 + 24x + -13 + 12x + (-13 + 12x) + 11y = 360 Remove parenthesis around (-13 + 12x) -23 + 24x + -13 + 12x + -13 + 12x + 11y = 360 Reorder the terms: -23 + -13 + -13 + 24x + 12x + 12x + 11y = 360 Combine like terms: -23 + -13 = -36 -36 + -13 + 24x + 12x + 12x + 11y = 360 Combine like terms: -36 + -13 = -49 -49 + 24x + 12x + 12x + 11y = 360 Combine like terms: 24x + 12x = 36x -49 + 36x + 12x + 11y = 360 Combine like terms: 36x + 12x = 48x -49 + 48x + 11y = 360 Solving -49 + 48x + 11y = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 48x + 49 + 11y = 360 + 49 Reorder the terms: -49 + 49 + 48x + 11y = 360 + 49 Combine like terms: -49 + 49 = 0 0 + 48x + 11y = 360 + 49 48x + 11y = 360 + 49 Combine like terms: 360 + 49 = 409 48x + 11y = 409 Add '-11y' to each side of the equation. 48x + 11y + -11y = 409 + -11y Combine like terms: 11y + -11y = 0 48x + 0 = 409 + -11y 48x = 409 + -11y Divide each side by '48'. x = 8.520833333 + -0.2291666667y Simplifying x = 8.520833333 + -0.2291666667y
| x^2+3x+2.25=0 | | .5(4x)=-20 | | 7-10=4 | | 2(6x+3)=18-3(-3x+16) | | r-3=2r+4 | | -6m+20-7(m-3)=7m-(3m-7)-9m+2 | | 3+2=5 | | -4x-6(-2x-7)=-22 | | 9t^2+32t+24=0 | | -(3w+4)+5(w-2)-3(6w-8)=10 | | 44=-4m-8 | | 7y+59x=345 | | 1=k+2 | | 2[d-(4d+9)+3]=2(d+6) | | -10r+3=-8+5r | | -56=-10r+4 | | 100=(x-1)+4(x-6) | | 3(x-6)-5(x+2)=-12 | | 3(x-2)=-6 | | -7x+6=2x-3 | | n-18=1-2 | | 2x+2(-4x+2)=76 | | 5(4x+p)=w | | 10y=9y+10 | | 5(4x+w)=p | | 10+3*d= | | 2-4=10 | | 5(2x+4)-3(5x+8)=0 | | 5x+5=6x+1 | | 4(2x-3)=32 | | 3x(4+3)+9(x-2)=0 | | 12x-74=100+6x |